The Effect of Interpersonal Communication on the Religious Behavior of Buddhist Monastery Manggala Ratna East Lampung - Arya Metta, Wahyu; Sutawan, Komang; Aprilianin Marwintaria Saputri, Vike (Journal of Education, Religious, and Instructions (JoERI), 2023)
This study was motivated by the problem of Buddhist religious behavior at the Manggala Ratna Buddhist Monastery in East Lampung, which includes a lack of activity in rituals and prayer, lack of enthusiasm for practicing religious teachings, lack of participation in religious activities, lack of a sense of obligation and awareness of the implementation of religious teachings, and lack of obedience to religious teachings. The research methodology uses a quantitative approach with descriptive methods. Data collection was done through a closed questionnaire that included statements about interpersonal communication variables (X) and religious behavior (Y). Data analysis includes validity test, reliability test, normality test, descriptive analysis, simple linear regression analysis, and hypothesis testing. The results showed that the influence of interpersonal communication on the religious behavior of Buddhists in Manggala Ratna Buddhist Monastery in East Lampung was 37.3%, while 62.7% was influenced by other factors not examined in this study. Regression analysis shows that there is a significant influence, with a significance value (sig) on the tcount of 7.032> ttable 1.663. Therefore, it can be concluded that interpersonal communication, especially in terms of openness, has a positive influence on the religious behavior of Buddhists at Manggala Ratna Buddhist Monastery in East Lampung.